Eye tracking in library and information science: a literature review. Issue 4 (21st November 2016) - Lund, Haakon
Abstract : Purpose: The purpose of this paper is to present a systematic literature review of the application of eye-tracking technology within the field of library and information science. Eye-tracking technology has now reached a level of maturity, which makes the use of the technology more accessible. Subsequently, a growing interest in employing eye tracking as a methodology within library and information science research must be anticipated. Design/methodology/approach: The review follows the guidelines set in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. Two reference databases are searched for relevant references: Library and Information Science Abstracts and Library, Information Science and Technology Abstracts. The main selection criteria are peer-reviewed literature that describes the experimental setting, including which eye-tracking equipment was used, the number of test persons and reports on the eye-tracking measures. Furthermore, this study will report which other methods were applied in combination with eye tracking. Findings: The number of published research utilizing eye-tracking technologies within library and information science (LIS) is still limited although an increase in the use of eye-tracking technologies is observed during recent years. Originality/value: To the knowledge of the author, this is the first systematic review on eye-tracking technology and application in LIS.